“English Polite Utterances” Terhadap Siswa/i Kelas XII SMA Nurul Hasanah Medan - Zuindra Zuindra; Bima Prana Chitra; Misla Geubrina (JPM: Jurnal Pengabdian Masyarakat, 2020)
In everyday life, a system that regulates how humans should get along is needed. The system of rules in this association is mutual respect which is usually called courtesy. Manners are very necessary, especially in communication. Politeness in communication must be instilled and developed in each individual. However, nowadays politeness speech has seemed to fade, especially among students. So, it is hoped that through the "English Polite Utterances" training activity, students can actively participate in developing sentences or politeness speech with interlocutors in everyday life. So with that, students will be accustomed to communicating politely, especially in request sentences in English, so that students' politeness will increase. To achieve this goal, it is done through training and deepening practice. Based on the results obtained, it can be concluded that politeness in communication must be instilled and developed in every student of SMA Nurul Hasanah Medan. The dialogue is composed of basic principles of politeness such as modals, please, the use of like and want and would.